Karakter Kuantitatif Kandidat Melon Hibrida (Cucumis melo L.) - Halimatus Sa'diyah; Suhartono Suhartono (Universitas Trunojoyo Madura, 2022)
Characterization is the first step in breeding to obtain information about a plant's character. This study aims to determine the character of the hybrid melon candidate. The research was carried out in the experimental garden of the Agrotechnology Study Program, Trunojoyo University, Madura, from September to December 2021. The research used a randomized block design with treatment using six hybrid melon candidates (G1, G2, G3, G4, G5, and G6) and two comparison varieties (Envy and Action 434) with three replications. The results showed that Candidate G2 had higher values of fruit diameter, flesh thickness, number of seeds, and fruit weight than the two comparison varieties. The highest sugar content value is found in candidate G4, which is 13.80%. Heritability values in the broad sense of quantitative characters ranged from 0.62-0.98, and there were correlations between characters (positive and negative) between the observed characters.